Nutrient contents in different sources of organic manures used in different farms of Bhaktapur district, Nepal - Sharma, Reena; Kandel, Saraswoti; Khadka, Sujan; Chaudhary, Suraj (Journal of Agriculture and Natural Resources, 2022)
Organic manure contributes carbonaceous matter to soil, which when decomposed, offers mineral nutrients to plants, also acts as a base exchange material, and helps to improve the physical, chemical, and biological aspects of soil. This study was conducted to assess the amount of total nitrogen, available phosphorous, available potassium, pH, under various organic manure sources. Collected organic matter samples were tested for total nitrogen, available phosphorus, available potassium, soil organic matter, and pH at the soil laboratory of Nepal Polytechnic College, Bharatpur-11, Chitwan, using the NARC, Soil Science Research Centre, Khumaltar, Lalitpur standard rating. The overall nitrogen concentration of goat dung was 1.667%, whereas buffalo manure had the lowest at 0.665%. The available phosphorus content of organic manure in the research area ranged from 0.732% in vermi-compost to 0.432% in compost, with substantial differences amongst manure samples. The goat manure had the highest potassium level (0.853%), whereas buffalo manure had the lowest (0.513%). The pH value of goat manure was 8.4 while the pH content of compost manure was 7.567. The maximum amount of organic matter (54.8) was found in buffalo manure, while the lowest (46.3) was found in vermi compost. The maximum amount of organic matter (54.8%) was found in buffalo manure, while the lowest (46.3%) was found in vermi compost. Modern technology must be adapted for successful and improved manure production. To increase the availability and maintenance of nutrients in organic manure, methods such as covering the manure to protect it from rain and sun, avoiding waterlogged conditions, and correct manure decomposition can be implemented.